Tuberculosis Peritonitis Patient with Septic Shock caused by Extended–Spectrum Beta Lactamases Producing Pseudomonas Aeruginosa - Suharjo B Cahyono; Neneng Ratnasari; Putut Bayupurnama; Catharina Triwikatmani; Siti Nurdjanah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
According to World Health Organization (WHO), tuberculosis (TB) is a worldwide pandemic. Up to 5% of patients with TB may have abdominal disease and 25-60% may have peritoneal involvement. Diagnosis of TB peritonitis is still challenging, and symptoms are usually insidious. The sensitivity of acid fast bacilli (AFB) is very low, ranging from 0-6%. Conventional mycobacterial culture takes up to 8 weeks to achieve results. Laparoscopic or laparotomy biopsy is uncomfortable for patient. The consequence of these problems is missing and delays in diagnosing TB peritonitis. In the end, it can results in significant morbidity and mortality. This case described a 20 year old female patient with TB peritonitis that suffered from septic shock caused by extended-spectrum beta lactamases (ESBL) producing Pseudomonas aeruginosa.  In this case, TB peritonitis was diagnosed based on clinical features, high levels of adenosine deaminase (ADA) and a positive rapid DNA test with Xpert MTB/RIF.  Keywords: tuberculosis peritonitis, extended-spectrum beta lactamases producing bacilli, adenosine deaminase, XpertMTB/RIF assay